2021
DOI: 10.5194/se-12-1143-2021
|View full text |Cite
|
Sign up to set email alerts
|

Seismic imaging across fault systems in the Abitibi greenstone belt – an analysis of pre- and post-stack migration approaches in the Chibougamau area, Quebec, Canada

Abstract: Abstract. Two high-resolution seismic reflection profiles acquired north and south of Chibougamau, located in the northeast of the Abitibi subprovince of Canada, help understand historic volcanically hosted massive sulfide (VMS) deposits and hydrothermal Cu–Au mineralization found there. Major faults crossed by the profiles include the Barlow fault in the north and the Doda fault and the Guercheville fault in the south, all targets of this study that seeks to determine spatial relationships with a known metal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The authors apply dip moveout corrections (DMO) and pre-stack time migration (PSTM) algorithms to obtain images of the main faults in the area, as well as identifying two diffraction sets that could be targeted in future exploration efforts. In their analysis, Cheraghi et al (2021) confirm that both techniques, DMO and PSTM, are very sensitive to irregularities in the acquisition geometry, in this case produced by the crooked footprint of the profiles as well as gaps of shots or receivers during the acquisition. This is, unfortunately, a common challenge in land seismic exploration, which can lead to misinterpretation of out-of-plane reflections.…”
Section: Seismic Methodsmentioning
confidence: 75%
“…The authors apply dip moveout corrections (DMO) and pre-stack time migration (PSTM) algorithms to obtain images of the main faults in the area, as well as identifying two diffraction sets that could be targeted in future exploration efforts. In their analysis, Cheraghi et al (2021) confirm that both techniques, DMO and PSTM, are very sensitive to irregularities in the acquisition geometry, in this case produced by the crooked footprint of the profiles as well as gaps of shots or receivers during the acquisition. This is, unfortunately, a common challenge in land seismic exploration, which can lead to misinterpretation of out-of-plane reflections.…”
Section: Seismic Methodsmentioning
confidence: 75%
“…Table 1 presents the geometrical attributes of the Swayze East survey. Cheraghi et al (2021) showed the effect of offset distribution for a crooked-line survey in a crystalline rock environment on common-offset Kirchhoff-style DMO No. of sweeps 1…”
Section: Dmo and Pstm Imaging Resultsmentioning
confidence: 99%
“…Another criterion could be the complexity of the subsurface architecture (i.e., dip and strike) wherever a crooked survey is acquired. These criteria define whether common midpoints (CMPs) contribute constructively or destructively after wave equation DMO or PSTM application (Cheraghi et al., 2021). In comparison, the weighting of the wave field in a receiver location by considering neighbouring traces makes the CM imaging algorithm independent from the geometry of the source–receiver pairs, as well as dip and strike of the geological formations (Hloušek et al., 2015a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations